2012
DOI: 10.1098/rspb.2012.0442
|View full text |Cite
|
Sign up to set email alerts
|

Neural sensitivity to sex steroids predicts individual differences in aggression: implications for behavioural evolution

Abstract: Testosterone (T) regulates many traits related to fitness, including aggression. However, individual variation in aggressiveness does not always relate to circulating T, suggesting that behavioural variation may be more closely related to neural sensitivity to steroids, though this issue remains unresolved. To assess the relative importance of circulating T and neural steroid sensitivity in predicting behaviour, we measured aggressiveness during staged intrusions in free-living male and female dark-eyed juncos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 75 publications
(140 reference statements)
3
98
1
1
Order By: Relevance
“…Thus, because male-male interactions typically elevate levels of testosterone (2), we must consider that any positive correlations between neurochemistry and behavior may be the product of male-male interactions and not the cause of it. For instance, ARO gene expression correlates positively with both aggression and plasma T in juncos (40). Nonetheless, most of the strongest relationships described here for neurochemistry and aggression are negative.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, because male-male interactions typically elevate levels of testosterone (2), we must consider that any positive correlations between neurochemistry and behavior may be the product of male-male interactions and not the cause of it. For instance, ARO gene expression correlates positively with both aggression and plasma T in juncos (40). Nonetheless, most of the strongest relationships described here for neurochemistry and aggression are negative.…”
Section: Discussionmentioning
confidence: 69%
“…This result strongly suggests that sensitivity to plasma steroid manipulations differs between the morphs. Other authors have suggested that steroid-sensitive behaviors are often better correlated with steroid receptors than with plasma steroid levels (10,11,(32)(33)(34). In dark-eyed juncos (Junco hyemalis), a relative of white-throated sparrows, aggressive responses to STI were positively correlated with ERĪ± mRNA expression in the ventral telencephalon, which contains MeA, and negatively correlated with it in the hypothalamus (11).…”
Section: Discussionmentioning
confidence: 99%
“…Morph differences in behavior cannot be entirely explained by these hormones, however, because the differences persist even when plasma levels are experimentally equalized (9). Individual variation in steroid-dependent behavior may be better explained by neural sensitivity to the hormones, for example by variation in the distribution and abundance of steroid receptors (10,11).…”
mentioning
confidence: 99%
“…Junco females vary in their level of same-sex aggression and maternal care [3,11,21,[36][37][38][39][40][41]. Aggressive females spend less time brooding and in some years produce smaller eggs, but provision more frequently [11].…”
Section: Introductionmentioning
confidence: 99%